Experimental research on heat transfer characteristic of HITEC molten salt in evacuated tube solar collector - Ji, Guo-Jian; Gu, Jin-Ming; Chen, Zhi; Lu, Bei-Bei; Gao, Ying (Frontiers in Energy Research, 2023)
HITEC molten salt (7% NaNO3, 53% KNO3, 40% NaNO2) has been identified as a suitable heat transfer fluid for concentrated solar power (CSP) systems, such as parabolic trough collectors (PTC) and evacuated tube solar collectors (ETSC). In order to optimize the flow and heat transfer performance of HITEC in ETSC, a molten salt heat transfer test rig was built to conduct an experimental study, varying inlet and outlet temperatures and mass flow rates of HITEC. Results show that the heat loss of HITEC in ETSC is lower than the other tubes. The convective heat transfer coefficient of HITEC is much lower than that of HITEC in round tube. Because the experimental data of HITEC in ETSC largely differed from the classical correlation equations, a new empirical heat transfer correlation equation was set for HITEC in ETSC, and the deviation between the experiment data and new correlation was within ±19.2%. Finally, by comparing the inlet and outlet temperatures of ETSC under different irradiation intensities, it is concluded that the ETSC can work stably when the temperature exceeds 700 W/m2.